Broiler Chicken Livestock Business Development Strategy in South Lampung Regency - Maryanti, Evi Valentina; Haryono, Dwi; Endaryanto, Teguh (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2023)
This study aims to to analyze the internal environment, analyze the external environment and, develop strategies for developing broiler chicken enlargement businesses. The data used is primary data for 2022 with a quantitative descriptive type of research. The method used the SWOT and QSPM analysis. This reaserch used primary and secondary datas. Primary data was used to answer questionnaire strategi development obtained by interview technique questionnaire. The results of the analysis show that the strategy for developing a broiler rearing livestock business is the utilization of a business location with a internally has the main strength in the form of the type of cage used and the main weakness in the form of the use of modern technology that has not been maximized. Externally, the main opportunity is in the form of established partnerships and the main threat is in the form of fluctuations in feed prices. Priority strategies that can be used for the development of Seandan Farm broiler rearing farms are:Utilization of business locations with a modern cage system to meet the high market demand for broiler chickens, utilization of raw material supplies from a partnership pattern that is established to meet the high consumption of broiler chickens, increasing the knowledge and skills of breeders through the use of modern technology in the business of raising broiler chickens, strengthening farmer capital through collaboration with other parties to maintain the quality of DOC, and improve the management of broiler housing systems by implementing standard operating procedure in order to tackle the spread of disease outbreaks in broiler chickens.